2017
DOI: 10.1097/mnm.0000000000000674
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the combination of a SPECT study with [123I]-FP-CIT of dopamine transporters and [123I]-MIBG myocardial scintigraphy in differentiating Parkinson disease from other degenerative parkinsonian syndromes

Abstract: ObjectiveMolecular imaging of nigrostriatal dopamine transporters (DAT) and sympathetic cardiac innervation with single-photon emission computed tomography (SPECT) are useful tools for differentiating idiopathic Parkinson disease (PD) from other degenerative parkinsonian syndromes (non-PD). Nevertheless, these modalities are often insufficient for achieving a definite diagnosis. The aims of this study were to evaluate the diagnostic accuracy of the combination of these tools.Materials and methodsThe SPECT radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Furthermore, mild to moderate accuracy has been reported for distinguishing PD from degenerative parkinsonian syndromes. 17,[20][21][22]35 It has been reported that the laterality of clinical symptoms in patients with PD contributes to the diagnosis of PD at an early stage. 36,37 On DAT-SPECT, the binding of ligands in the most affected side, which is the opposite side as the symptoms, results in a lower value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, mild to moderate accuracy has been reported for distinguishing PD from degenerative parkinsonian syndromes. 17,[20][21][22]35 It has been reported that the laterality of clinical symptoms in patients with PD contributes to the diagnosis of PD at an early stage. 36,37 On DAT-SPECT, the binding of ligands in the most affected side, which is the opposite side as the symptoms, results in a lower value.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to overcome the shortcomings of each modality, the combination of DAT-SPECT and MIBG myocardial scintigraphy has been investigated for finding out PD in patients with parkinsonian syndrome. [13][14][15][16][17][18][19][20][21][22][23] According to the recent studies, Yoshii et al reported the combination of the SBR in DAT-SPECT and H/M ratio (delayed) in MIBG myocardial scintigraphy, using cut off values of less than 4.5 for the SBR and less than 2.2 for the H/M ratio (delayed) showed moderate accuracy (77.1%) in differentiating PD from APD. 20 Uyama et al reported the combination of the SBR in DAT-SPECT and H/M ratio (delayed) in MIBG myocardial scintigraphy, using cut off values of less than 3.24 for the SBR and less than 2.745 for the H/ M ratio (delayed) showed moderate accuracy (79.4%) in differentiating PD from APD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate diagnosis of PD can be challenging, remaining complex to differentiate PD from other parkinsonian syndromes (Uyama et al., ). Recently, molecular imaging techniques using single‐photon emission computed tomography (SPECT) have been widely employed in the identification of dopamine deficit, assessing the dopamine transporters (DAT) depletion (Brooks, ).…”
Section: Introductionmentioning
confidence: 99%
“…This criterion has been recommended for the evaluation of PD in clinical practice 10,11 . Different ligands of DAT have been successful suggested in Positron Emission Tomography (PET) imaging scintigraphy and Single Photon Emission Computerized Tomography (SPECT) radioisotope scintigraphy for the diagnosis of PD 12 .…”
mentioning
confidence: 99%